Clinical characteristics of foot ulceration in people with chronic gout. Issue 2 (28th March 2014) - Rome, Keith; Erikson, Kathryn; Otene, Cynthia; Sahid, Hazra; Sangster, Karyn; Gow, Peter
Abstract: Gout is the most common form of inflammatory arthritis and it has an affliction to the foot. Foot involvement in gout has been linked to foot pain, impairment and disability. There has been limited research on the effect of ulceration on foot pain, impairment, disability and health‐related quality of life in patients already living with gout. The aim of the study was to describe the wound characteristics and the effect on foot pain, disability and health‐related quality of life in patients with foot ulceration associated with gout. Participants were recruited from rheumatology clinics in Auckland, New Zealand. All the current foot ulceration sites and wound characteristics were recorded using the TIME wound assessment tool. The outcome measures included general pain, patient global assessment scale, foot pain, disability and impairment. Participants completed the Cardiff Wound Impact Schedule to assess the effect of ulcers on health‐related quality of life. Sensory loss, vibrational thresholds and ankle brachial pressure index were collated to assess for lower limb arterial disease. Six participants were predominantly older men with a long duration of gout, high rates of obesity and co‐morbidities such as hypertension, hyperlipidaemia, diabetes and cardiovascular disease. The mean (SD) duration of the foot ulcers was 4 (2) months. The majority of foot ulcers observed were 0·5 cm 2 or smaller superficial thickness with surrounding callus. Partial thickness and full‐thickness ulcers were also observed. Two patients presented with ulcers on multiple sites. There was only one case of infection. Gouty tophi were evident in most of the wounds. The dorsal aspect of the third toe was found to ulcerate in most cases. Moderate scores of foot pain, disability, impairment and health‐related quality of life were observed. Most participants wore shoes deemed as poor. Foot ulceration in gout is chronic and multiple ulcers can occur with the potential of leading to delayed wound healing, infection and a reduced quality of life. Poor footwear may contribute to the development and delayed healing of ulceration in people with gout.